2020
DOI: 10.3390/nu13010098
|View full text |Cite
|
Sign up to set email alerts
|

Poor Sensitivity of Fecal Gluten Immunogenic Peptides and Serum Antibodies to Detect Duodenal Mucosal Damage in Celiac Disease Monitoring

Abstract: A lifelong gluten-free diet (GFD) is the only current treatment for celiac disease (CD), but strict compliance is complicated. Duodenal biopsies are the “gold standard” method for diagnosing CD, but they are not generally recommended for disease monitoring. We evaluated the sensitivity and specificity of fecal gluten immunogenic peptides (GIPs) to detect duodenal lesions in CD patients on a GFD and compared them with serum anti-tissue transglutaminase (tTG) IgA antibodies. A prospective study was conducted at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…Other authors also found a significant association between patient self-reported gluten consumption and GIP detection. GIP was detected in 52.9% of patients who suspected gluten intake in the last month in comparison to 16.3% for those who were not aware of any gluten exposure[ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Other authors also found a significant association between patient self-reported gluten consumption and GIP detection. GIP was detected in 52.9% of patients who suspected gluten intake in the last month in comparison to 16.3% for those who were not aware of any gluten exposure[ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other authors reported a weaker association between evident gluten exposure, as measured by GIP detection in urine and stool, and persistent villous atrophy[ 29 , 30 , 45 ]. In the DOGGIE BAG study referred to above, at least one GIP-positive sample was found in 7 of 11 patients with normal serology, and 2/3 of them had persistent villous atrophy (Marsh IIIa) after 24 mo of follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations